Catheter replacement combined with antiplatelet therapy in hemodialysis catheter-related right atrial thrombus: a potential treatment approach - Jibo Sun; Yu Liu; Jiehao Chen; Yaojia Zhou; Hong Fan; Qiuyan Zhao (BMC Cardiovascular Disorders)
Abstract Background Catheter-related right atrial thrombus (CRAT) is a severe complication in hemodialysis patients that can lead to catheter dysfunction and pulmonary embolism (PE). However, no standardized treatment strategy currently exists for hemodialysis-related CRAT. This study aims to investigate the efficacy of catheter replacement and antiplatelet therapy in managing hemodialysis CRAT. Methods We conducted a retrospective cohort study on patients at West China Hospital diagnosed with catheter dysfunction caused by right atrial thrombosis between May 2019 and March 2022. All CRAT were asymptomatic and underwent catheter replacement (either guidewire exchange or insertion at a new site), with the new catheter tip repositioned away from the original location and closer to the right atrium. Antiplatelet therapy with dipyridamole was initiated post-procedure. We analyzed the efficacy of catheter replacements and antiplatelet therapy in hemodialysis-related CRAT. Results Among the 178 patients with CRAT who underwent catheter replacement, the success rate was 98.9%. Preoperative examinations detected asymptomatic PE in 10 patients (5.6%). During follow-up, 3 patients (1.9%) developed new asymptomatic PE post-operation, and no fatal PE occurred. The catheter primary patency rates at 3, 6, and 12 months were 87.0%, 62.6%, and 36.7%, respectively. The secondary patency rates were 91.7%, 75.7%, and 52.3% at 3, 6, and 12 months, respectively. No patients died due to PE or other thrombotic complications. Conclusions Catheter replacement combined with antiplatelet therapy may be a potential treatment approach for patients with hemodialysis-related CRAT < 6 cm, without other complications except from catheter dysfunction.